Moment to force ratio characteristics of three Japanese NiTi and TMA closing loops - Kum Mark; Quick Andrew; Hood James A.; Herbison Peter (Sciendo, 2004)
Objectives: This in vitro study investigated the loads ("forces"), moments and moment:force ratios (M:F) generated during activation and deactivation of three closing loop designs constructed from two different orthodontic wire alloys.